Proses Sertifikasi Halal di Indonesia dari Perspektif Regulator dan Praktisi Industri - Maulana Maulana; Nasrullah Bin Sapa; Mukhtar Galib; Cut Muthiadin (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2025)
The halal certification process in Indonesia is crucial in meeting the needs of both domestic Muslim consumers and the international market. This study examines the perspectives of regulators and industry practitioners on halal certification in Indonesia, focusing on regulatory complexity, procedural challenges, and market-driven compliance. Using a descriptive qualitative approach, the study identifies key issues, including the overlap of responsibilities among regulatory bodies, the impact of digital transformation, and the importance of government-industry collaboration. Findings reveal that regulatory complexity often creates procedural confusion, hindering compliance. BPJPH’s digital initiatives present opportunities to streamline certification but face accessibility challenges, particularly for SMEs in rural areas. Additionally, strong consumer demand for halal products pressures companies to prioritize halal certification as part of their competitive strategy. This study’s implications suggest a need for an integrated approach in Islamic studies involving religious, policy, and business disciplines to develop a responsive Sharia-based economy. Enhancing collaboration between regulators and industry is critical to support the growth of Indonesia's halal sector and strengthen its position in the global halal market.